Discrimination and Education Quality Moderate the Association of Sleep With Cognitive Function in Older Black Adults: Results From the Einstein Aging Study. (24th November 2022) - Ji, Linying; Zhaoyang, Ruixue; Jiao, June L; Schade, Margeaux M; Bertisch, Suzanne; Derby, Carol A; Buxton, Orfeu M; Gamaldo, Alyssa A
Abstract: Objectives: Heterogeneity among Black adults' experiences of discrimination and education quality independently influence cognitive function and sleep, and may also influence the extent to which sleep is related to cognitive function. We investigated the effect of discrimination on the relationship between objective sleep characteristics and cognitive function in older Black adults with varying education quality. Method: Cross-sectional analyses include Black participants in the Einstein Aging Study ( N  = 104, mean age = 77.2 years, 21% males). Sleep measures were calculated from wrist actigraphy (15.4 ± 1.3 days). Mean ambulatory cognitive function (i.e., spatial working memory, processing speed/visual attention, and short-term memory binding) was assessed with validated smartphone-based cognitive tests (6 daily). A modified Williams Everyday Discrimination Scale measured discriminatory experiences. Linear regression, stratified by reading literacy (an indicator of education quality), was conducted to investigate whether discrimination moderated associations between sleep and ambulatory cognitive function for individuals with varying reading literacy levels. Models controlled for age, income, sleep-disordered breathing, and sex assigned at birth. Results: Higher reading literacy was associated with better cognitive performance. For participants with both lower reading literacy and more discriminatory experiences, longer mean sleep time was associated with slower processing speed, and lower sleep quality was associated with worse working memory. Later sleep midpoint and longer nighttime sleep were associated with worse spatial working memory for participants with low reading literacy, independent of their discriminatory experiences. Discussion: Sociocultural factors (i.e., discrimination and education quality) can further explain the association between sleep and cognitive functioning and cognitive impairment risk among older Black adults.